2004
DOI: 10.1063/1.1799240
|View full text |Cite
|
Sign up to set email alerts
|

[ 110 ] Orientated lead salt midinfrared lasers

Abstract: A Lead salt midinfrared quantum-well (QW) laser on [110] orientation is proposed. Theoretical simulations of [110] QW edge-emitting lasers show a 70° temperature increase in continuous-wave operation compared to the conventional [100]-orientated lasers. This is because the gain on [100]-orientated QW structure is significantly increased. Among [100], [111], and [110] orientations, [110]-orientated QW structure offers the highest gain. PbSe∕PbSrSe QW structures were successfully grown on [110]-orientated BaF2 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…It is worthwhile pointing out that this high PL intensity is an indication of high material quality and has no direct connection with the high material gain we have predicted in Ref. [1,2]. Rather, a thin QW structure which would lift off the degeneracy is needed to achieve the higher gain predicted for the [1 1 0]-orientated material.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…It is worthwhile pointing out that this high PL intensity is an indication of high material quality and has no direct connection with the high material gain we have predicted in Ref. [1,2]. Rather, a thin QW structure which would lift off the degeneracy is needed to achieve the higher gain predicted for the [1 1 0]-orientated material.…”
Section: Resultsmentioning
confidence: 76%
“…IV-VI lead salt semiconductor materials have been used to fabricate mid-infrared optoelectronic devices on (0 0 1) and (1 1 1) substrates but to our knowledge, never on (1 1 0) substrates. However, our simulations show that the highest material gain for IV-VI MQW structures may be obtained [1 1 0]-oriented growth [1,2]. High material gain is a much desired property for active devices such as diode lasers.…”
Section: Introductionmentioning
confidence: 97%
“…IV–VI QWs have been successfully fabricated with growth directions along 〈111〉, 〈100〉, and 〈110〉 11, 14, 15. For QWs grown along [111] direction, the four‐valley degenerate at four L points splits into one longitudinal and three oblique branches.…”
Section: Physical Model and Mathematical Formulationmentioning
confidence: 99%
“…This effect was recently considered for evaluating gain in IV-VI MQWs with different orientations [32,33], and results showed that (111)-oriented wells will have lower lasing thresholds than either (100) or (110) oriented wells. This effect was recently considered for evaluating gain in IV-VI MQWs with different orientations [32,33], and results showed that (111)-oriented wells will have lower lasing thresholds than either (100) or (110) oriented wells.…”
Section: Iv-vi Quantum Well Materialsmentioning
confidence: 99%